Books before print - Kwakkel, Erik, 1970- (Medieval media cultures., 2018)
"This beautifully illustrated book provides an accessible introduction to the medieval manuscript and what it can tell us about the world in which it was made and used. Captured in the materiality of manuscripts are the data enabling us to make sense of the preferences and habits of the individuals who made up medieval society. With short chapters grouped under thematic headings, Books Before Print shows how we may tap into the evidence and explores how manuscripts can act as a vibrant and versatile tool to understand the deep historical roots of human interaction with written information. It highlights extraordinary continuities between medieval book culture and modern-world communication, as witnessed in medieval pop-up books, posters, speech bubbles, book advertisements, and even sticky notes."--Provided by publisher.